Efeitos da oxigenoterapia hiperbárica após isquemia hepática segmentar normotérmica e reperfusão, em coelhos: avaliação bioquímica, morfológica e da microcirculação hepática pelo ultra-som contrastado - Maria Cecilia Souto Lucio de Oliveira (2008)
Interruption of blood flow to an organ or tissue (ischemia) and subsequent reperfusion lead to an acute inflammatory response that may cause significant cellular damage and organ dysfunction. It is called ischemia/reperfusion injury. Hepatic ischemia/reperfusion injury is characterized by circulatory and metabolic derangements, liver dysfunction and tissue damage. There were a large number of strategies to protect the liver from injuries caused by ischemia and reperfusion, like surgical and pharmacologic strategies and gene therapy. Hyperbaricoxygen therapy (HBO) is an effective adjunct in treating ischemia-reperfusion injury of brain, small intestine, testis and crushing extremities. Some studies were designed to test the effect of hyperbaric oxygen therapy to protect the liver against ischemia/reperfusion injury.The objective of this study was to asses changes of hepatic microvascular perfusion (microbubble-enhanced ultrasonography) as related to hepatic morphology and hepatocellular integrity (serum aspartate aminotransferase- AST, alanine aminotransferase- ALH and lactic dehydrogenises- LDH). Twenty-two male New Zeeland rabbits were subjected to 60 minutes of normotermic, segmental, hepatic ischemia, followed by 60 minutes of reperfusion. The HBO group (n=12), wasexposed to one session of 60 minutes of hyperbaric oxygen after reperfusion. Ten rabbits maintained under normobaric room air served as controls. Microbubbleenhanced ultrasonography was performed 24 hours after reperfusion in the 22 rabbits. Serum AST, ALT and LDH were determined in samples collected before ischemia, 10 minutes and 24 hours after hepatic reperfusion. Hepatic morphology was evaluated by macroscopic and light microscopy study of paraffin-embeddedsections stained by hematoxylin and eosin. Hyperbaric oxygen therapy after ischemia and reperfusion didnt modify serum AST, ALT and LDH activities, attenuated the hepatic microvascular perfusion impairments at microbubble-enhanced ultrasonography and didnt modify the histological finds.